PENGEMBANGAN TUTORIAL MERANCANG MULTIMEDIA PEMBELAJARAN INTERAKTIF UNTUK GURU PAI - Arief Ardiansyah (Edudeena : Journal of Islamic Religious Education, 2020)
Abstract: Insturctional media is a component that can not be separated from instructrional activities. One format of learning media that is applied in classroom learning activities is interactive learning multimedia (MPI). However, unfortunately the teacher's limited ability to develop it. Therefore, this research and development attempt to develop a tutorial on designing and developing learning multimedia. The method of developing this tutorial applies the stages of learning multimedia design from Lee and Owens. The subjects of this study were the teachers in Bajangan State Elementary School, Pasuruan Regency. The effectiveness of media tutorials is tested by media experts, material experts, and by media design experts. While the field testing itself is carried out by the teachers. From various tests, the tutorial media can be said to be feasible as learning media. The final form of the developed tutorial media is an excecutable (.exe) program that is packaged into compact discs. Abstrak: Media pembelajaran merupakan komponen yang tidak dapat dipisahkan dari kegiatan pembelajaran. Salah satu format media pembelajaran yang diterapkan dalam kegiatan pembelajaran di kelas adalah multimedia pembelajaran interaktif (MPI). Namun, sayangnya keterbatasan kemampuan guru untuk mengembangkannya. Oleh karena itu, penelitian dan pengembangan ini berusaha mengembangkan suatu tutorial merancang dan mengembangkan multimedia pembelajaran. Metode pengembangan tutorial ini menerapkan tahap-tahap desain multimedia pembelajaran dari Lee dan Owens. Subjek penelitian ini adalah para guru di lingkungan SD Negeri Bajangan Kabupaten Pasuruan. Keefektifan media tutorial diuji oleh ahli media, ahli materi, dan oleh ahli desain media. Sedangkan uji lapangan sendiri dilakukan oleh para guru. Dari berbagai uji tersebut, media tutorial dapat dikatakan layak sebagai media pembelajaran. Wujud akhir dari media tutorial yang dikembangkan adalah berupa program excecutable (.exe) yang dikemas ke dalam keping compact disc.